(untitled) (Fiep Bulletin - online, 2024)
Introduction: Growth hormone (GH) is an anabolic hormone that is often used by athletes and people who go to gyms with the aim of increasing muscle mass, however it is known that this proliferative hormone can cause undesirable effects on the body, this study was designed to mimic the use of GH along with resistance training in young people in the growth phase. Objective: The aim of this study was to verify the effect of GH administration associated or not with physical training on serum biochemistry, body weight and organ weight in Wistar rats. Methods: The rats were divided into four groups (n=10): CT (control group); GH (group with administration of 0.2 IU/Kg of GH); TR (resistance training group); and TRGH (group submitted to resistance training and GH). After 30 days, serum biochemistry, animal weight, organ weight and abdominal length and circumference were measured. Results: The GH group had greater final body length and greater testicular weight and the GHTR group had less retroabdominal fat. Conclusion: It is concluded that the administration of GH in young people results in increased body growth, only when not associated with resistance training. When GH is combined with resistance training, it results in the reduction of retro-abdominal fat, which has an important cardioprotective effect, but it increases CK-MB levels, which indicates cardiac wear due to resistance training. At the dose used and time used, GH does not alter the lipid profile or blood glucose levels of non-obese animals. Keywords: physical exercise, fat, bodybuilding, testicle, males.